Redesign of DPD RI’s Authority for Monitoring and Evaluation Raperda dan Perda as Derivative Supervision - Mufidah, Nuruz Zakiyatul; Habibi, Miftakhur Rokhman; Sudarsono, Galih Putri; Ngaisah, Siti (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
There is a change in the scheme of monitoring draft local regulations (Raperda) and local regulations (Perda) since the amendment of Law No. 17/ 2014 about MPR, DPR, DPD, and DPRD. This amendment was made through Law No. 2 /2018 by adding Article 249 paragraph (1), letter j, by providing new authority for the House of Regional Representatives (DPD RI). The new authority of the DPD RI is to monitor and evaluate the draft local regulations (Raperda) and local regulations (Perda). The problem is that in the Indonesian constitutional system, the supervision of the draft local and local regulations is not the territory of DPD RI. So, it is true that the authority is given but cannot be implemented. The research concluded that derivative supervision can help translate DPD RI’s new authority to oversee regional legal products.